1980
DOI: 10.1007/bf00433815
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine stereotypies and polyribosomal disaggregation in rats: Effects of adrenergic and serotonergic blocking agents

Abstract: To find the specific chemical moiety responsible for the disaggregation of polyribosomes after induction of aberrant behavior by d-amphetamine, specific amine blockers and reserpine were utilized. It appears that dopamine is responsible for both the disaggregation of polyribosomes and stereotypic behavior while the roles of serotonin and norepinephrine are not significant in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Although a complete consideration of amphetamine pharmacology is beyond the scope of this presentation, it may be noted that considerable early evidence suggested that 8-adrenergic mechanisms are primarily involved in amphetamine-induced glycogenolysis (Estler and Ammon, 197 l;Hutchins and Rogers, 1971;Nahorski and Rogers, 1975), whereas dopaminergic effects have been associated with hyperthermic as well as hypothermic actions of the drug (Yehuda and Wurtman, 1972;Ulus et al, 1975;Jon and Caccia, 1975). Consistent with the present observations, dopamine antagonists attenuate both amphetamine-induced hyperthermia and its effects on protein synthesis ( Moskowitz et al, 1975;Widelitz et al, 1977;Widelitz and Hable, 1980). As discussed previously, tolerance to both amphetamine-induced glycogenolysis and drug-induced hyperthermia develop in parallel (Nahorski and Rogers, 1975).…”
Section: Discussionsupporting
confidence: 91%
“…Although a complete consideration of amphetamine pharmacology is beyond the scope of this presentation, it may be noted that considerable early evidence suggested that 8-adrenergic mechanisms are primarily involved in amphetamine-induced glycogenolysis (Estler and Ammon, 197 l;Hutchins and Rogers, 1971;Nahorski and Rogers, 1975), whereas dopaminergic effects have been associated with hyperthermic as well as hypothermic actions of the drug (Yehuda and Wurtman, 1972;Ulus et al, 1975;Jon and Caccia, 1975). Consistent with the present observations, dopamine antagonists attenuate both amphetamine-induced hyperthermia and its effects on protein synthesis ( Moskowitz et al, 1975;Widelitz et al, 1977;Widelitz and Hable, 1980). As discussed previously, tolerance to both amphetamine-induced glycogenolysis and drug-induced hyperthermia develop in parallel (Nahorski and Rogers, 1975).…”
Section: Discussionsupporting
confidence: 91%